The effectiveness of Insecticide-Treated Nets applications in malaria endemic areas of Tanah Bumbu District - Nita Rahayu; Sri Sulasmi; Yuniarti Suryatinah (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2018)
Background : Disease control is transmitted by mosquitoes are mostly done, one of them the use of insecticide-treated bed nets, mosquito nets coated with mosquito repellent and not harmful to health. The aim of this research is to know the effectiveness of application of insecticide treated mosquito nets in malaria vector control in Tanah Bumbu Regency.Methods :Quantitative research methods, cross sectional design and quasi experiments. Population, the entire population get a mosquito net. Samples, residents willing to take blood, interviewed. Determination of sample behavior and Mass Blood Survey of 100 respondents using purposive sampling.Results: MBS 100 samples, positive 7 respondents 2 org plasmodium vivax, 5 org plasmodium falciparum. The result of the behavior of insecticide treated bed nets (53%) of respondents received and used bed nets and (47%) received and not used. Result of bio essay test 20 mosquito net and 2 control show 5 mosquito net still effective killing An mosquito. Aconitus, with 82,67- 100% mortality, while 15 other bed nets are ineffective.Conclusion : The conclusion is the decrease of malaria case after use of mosquito net with SPR 7%. Recommendation, to forest workers to keep wearing insecticide-treated bed nets, using repellents and taking prophylactic drugs while working in the forest.Â Keywords: Effectiveness, insecticide-treated nets, Anopheles